Structural, morphological, and non-linear optical properties of thermally evaporated neodymium doped zinc oxide thin films. (16th March 2023) - Yadav, Sunny; Barala, Monika; Dhar, Rakesh; Mohan, Devendra
Abstract: The thermal evaporation procedure has been used in the current work to synthesize various compositions of neodymium-doped zinc oxide thin films with varied thicknesses on glass substrates. The Films have a hexagonal wurtzite structure, according to x-ray Diffraction (XRD) study, and the structure has not changed after doping of Neodymium. Raman spectroscopy revealed peaks at 100.49, 331, 434, 574, and 581 cm −1 that supported the ZnO phase, and the intensity of the peaks reduced as the number of dopants rose. FTIR analysis verified that Nd had completely dispersed in ZnO. The calculations of the bandgap (Eg ) and absorption coefficient ( α ) are done using absorption spectra. The Z-Scan method has been employed to assess nonlinear optical characteristics for all Nd-doped ZnO thin films. The samples show the change from saturable absorption (SA) to reverse saturable absorption (RSA), the process of focusing to self-defocusing, and vice versa. This is due to the fact that the two-photon process is more potent than the one-photon process. The acquired value of the third-order optical non-linear susceptibility χ (3) is of the order of 10 −5 to 10 −6 (e.s.u.) that makes the samples suitable for use in various photonic applications like using as an optical limiter and/or optical switch due to higher values of optical non-linear parameters.